ESP: english for economists - Gryshchenko, O. V. (My University, 2015)
English for Specific Purposes (ESP) is a specific approach oriented to senior students (adults) whose aim is to learn English in order to communicate a set of professional skills and to perform particular job related functions.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; technologies combined; технології в поєднанні; технологии в сочетании; економіст; экономист; economist